The History of the Cross-Section of Stock Returns - Linnainmaa, Juhani T; Roberts, Michael R (Review of Financial Studies, 2018)
Using data spanning the twentieth century, we show that the majority of accounting-based return anomalies, including investment, are most likely an artifact of data snooping. When examined out-of-sample by moving either backward or forward in time, the average returns and Sharpe ratios of most anomalies decrease, whereas their volatilities and correlations with other anomalies increase. The few anomalies that do persist out-of-sample correlate with the shift from investment in physical capital to intangible capital and the increasing reliance on debt financing over the twentieth century. Received November 25, 2016; editorial decision September 23, 2017 by Editor Andrew Karolyi. Authors have an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.